Penerapan Metode Analitycal Hierarchy Process dalam Sistem Pendukung Keputusan Kelayakan Rumah Tangga Penerima Listrik Gratis - Siti Andini Utiarahman; Hastuti Dalai (STMIK Budi Darma, 2022)
One of the government programs includes free electricity connection assistance for underprivileged households through the Targeted Electricity Subsidy (SLTS) program. In implementing the SLTS program, recipients of free electricity must meet several predetermined criteria to qualify as recipients. Every year there are a lot of registrants for RT candidates who receive free electricity in Gorontalo province, so obtaining information takes a long time because accuracy is required in the selection process to determine the eligibility of RT candidates to receive free electricity. The purpose of the study was to apply the AHP method to the decision support system for the eligibility of households receiving free electricity by calculating the value of the priority results of the sub-criteria and the feasibility value. The calculation process is carried out based on the criteria, the results of the priority sub-criteria are obtained where the applicant with a feasibility value = 1 gets a decent status. On the other hand, applicant 2 with a sub-criteria priority of 0.2983 and applicant 3 with a sub-criteria priority of 0.0847 gets an unfeasible status because the value obtained is < 1. So it can be concluded that the AHP method can be used in a decision support system to assist related parties in determining the eligibility of households receiving free electricity